FROM DISTANT NEIGHBOURS TO BEDMATES: EXPLORING THE SYNERGIES BETWEEN THE SOCIAL ECONOMY AND SUSTAINABLE DEVELOPMENT. (21st April 2017) - HUDON, Marek; HUYBRECHTS, Benjamin
ABSTRACT: To introduce this special issue we explore the conceptual and practical synergies between the social economy and sustainable development. New empirical evidence is presented on the emergence of these two research fields and the increasing combination of these fields in the literature. Several avenues through which social enterprises can contribute to the transition towards sustainable development are then identified. This is followed by a discussion of how and why the combination can be particularly fruitful both for the social economy and for sustainability transition movements. We also highlight some important challenges facing the social economy with regard to its contribution to sustainable development. Finally we introduce the papers that constitute this special issue and show how they contribute, individually and collectively, to a better understanding of the increasing linkage between the social economy and sustainable development.